Constraints on spin-3/2 and excited spin-1/2 fermions coming from the leptonic Z0-partial width - Montero, J. C. [UNESP]; Pleitez, Vicente [UNESP] (Elsevier, 1994)
We consider effective interactions among excited spin-1/2 and spin-3/2 leptons with the usual ones. Assuming that these new leptons are lighter than the Z0, we study the constraints on their masses and compositeness scale coming from the leptonic Z0 partial width.